Anaphylaxis to foods purchased from food establishments in Australia. (14th July 2021) - Zurzolo, Giovanni A; Campbell, Dianne E; Said, Maria; Peters, Rachel L; Dharmage, Shyamali C
Abstract : Aim: Food establishments that sell non‐packaged foods are not required to have a food label directly on the food product detailing the ingredients. This practice could increase the risk of anaphylaxis among individuals with food allergy. The aim of the study is to understand whether anaphylaxis occurs commonly in individuals with food allergy as a consequence of eating food products purchased from food establishments. Methods: We undertook an anonymous on‐line cross‐sectional survey of food allergic individuals over a 9‐month period. Anaphylaxis was defined as reported symptoms consistent with the Australasian Society of Clinical Immunology and Allergy definition of anaphylaxis. Results: A total of 268 responses were received over the study period and 264 consented and completed the questionnaire. Among our survey participants, the rate of anaphylaxis to food purchased from establishments was 27% ( n = 67/246, 95% confidence interval 21.8–33.3%). Of those who reported an anaphylaxis ( n = 67), 87% reported informing staff of their/their dependents food allergy/s. Most (81%) reported that they would like to see additional information, such as listing of allergen information next to dishes on the menu and 61% reported that staff pro‐actively asking about food allergies would be beneficial. Conclusion: Anaphylaxis from food purchased at food establishments is not uncommon despite a high proportion of individuals declaring their food allergy to staff. Consumers with food allergy would like to see allergen information listed on the menus and for staff to proactively enquire about food allergies. A food allergen matrix that is regularly checked/updated so staff and consumers have easy access to information on menu items and common allergens is required.